China and Its Neighbours - Edited by; Kondapalli, Srikanth and Mifune, Emi (New Delhi Pentangon Press, 2010)
Contributed articles presented at a conference held at New Delhi in November 2008.
Include Index, Tables, Graphs, Maps and Annexurres
Keywords: China -- ChinaDiplomatic relations